Ecological Interface for Collaboration of Multiple UAVs in Remote Areas. Issue 19 (2016) - van Lochem, S.; Borst, C.; de Croon, G.C.H.E.; van Paassen, M.M.; Mulder, M.
Abstract: Unmanned Aerial Vehicles (UAVs) can be used to access remote areas, e.g., for surveillance missions. Collaboration between them can help overcome communication constraints by building airborne relay networks that allow beyond line of sight communication. This research investigates whether a single human operator can supervise multiple UAVs in a collaborative surveillance task under communication constraints. We designed an ecological interface to support operators in their task and increase system flexibility. A preliminary humanin-the-loop study was done to investigate operator task performance and evaluate interface components. It was shown that operators are able to successfully operate surveillance missions under communication- and battery constraints. Participants did, however, not succeed to do this without separation conflicts and communication losses, which indicates that the interface lacks elements representing endurance and separation assurance. To an extent, the interface design turned out to be scalable, with a few remaining visualizations that cause clutter for large numbers of UAVs. More advanced ways of displaying information on request and grouping of select information is warranted to further improve the interface.